Learning motivation and self-efficacy of Indonesian international students in Malaysian universities: A structural equation modeling (SEM) approach - Handrianto, Ciptro (Journal of International Students, 2026)
This study investigates the structural relationship between academic self-efficacy and learning motivation—both intrinsic and extrinsic—using structural equation modeling (SEM). A total of 402 Indonesian students enrolled in five Malaysian universities participated by completing a validated online questionnaire. The findings reveal that academic self-efficacy strongly predicts both intrinsic and extrinsic motivation, with a more robust effect on the former. In turn, intrinsic motivation significantly contributes to self-efficacy and academic performance, whereas extrinsic motivation has a limited influence. The reciprocal effects between self-efficacy and motivation support the frameworks of social cognitive theory and self-determination theory, highlighting the psychological adaptability of students in culturally adjacent yet institutionally distinct environments. The study offers theoretical and practical insights into fostering student agency and sustainable learning motivation in international education, particularly within Southeast Asia.